2018
DOI: 10.1111/tbed.12877
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological surveillance of Hepatitis E virus in wild and domestic carnivores in Brandenburg, Germany

Abstract: Hepatitis E virus (HEV) is a zoonotic virus which circulates in pigs and wild boars as main reservoir species. To reveal the infection rate in carnivores, we have carried out a monitoring study of raccoons, raccoon dogs, dogs and cats sampled in Brandenburg, Germany. In summary, 53.8% (43 of 80) of the raccoons, 34.3% (25 of 73) of the raccoon dogs, 56.6% (47 of 83) of dogs and 32.3% (21 of 65) of cats were tested positive for HEV-specific antibodies. No viral RNA could be detected. This first description of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 11 publications
4
25
4
Order By: Relevance
“…These food items have been suggested to be a source of HEV (10,12,39) and are frequently imported to Northern Norway. Recently, an anti-HEV IgG seroprevalence of 56.6% and 32.2% was found in dogs and cats in Germany (40). Since no viral RNA could be isolated, the genotype is still not known.…”
Section: Discussionmentioning
confidence: 99%
“…These food items have been suggested to be a source of HEV (10,12,39) and are frequently imported to Northern Norway. Recently, an anti-HEV IgG seroprevalence of 56.6% and 32.2% was found in dogs and cats in Germany (40). Since no viral RNA could be isolated, the genotype is still not known.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the prevalence of HEV in domestic pets in the Netherlands, we have collected serum samples from 162 dogs, we found that 18.52% (30/162) dogs were positive for anti-HEV antibodies in serum. Literature data on the seroprevalence of HEV antibodies in dogs ranges from 0.8% in UK [11], 28.2% in South Korea [7], 13.54 to 36.55% in different regions of China [6,[12][13][14], and 56.6% in Germany [15]. Genomic HEV RNA was not detectable in these serum samples by qRT-PCR.…”
Section: Resultsmentioning
confidence: 83%
“…Although other alternatives to serum have been tested for the detection of anti-HEV antibodies, they are scarce, and the results have not always been compared with the serum results. A previous study detected anti-HEV antibodies in body cavity transudate obtained from raccoons, raccoon dogs, cats, and dogs [47]. Meat juice has also been used in some studies to determine HEV seroprevalence in hunted wild boars and slaughtered pigs with satisfactory results [48,56].…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme-linked immunosorbent assay (ELISA) technique is the main diagnostic method to perform HEV surveillance studies, and many commercial and 'in-house' kits have been described [44][45][46]. Serum samples are typically used to assay anti-HEV antibodies, although meat juice and body cavity transudate have also been used in a few studies [47,48]. To detect the presence of HEV RNA, several reverse transcriptase-polymerase chain reactions (RT-PCR) techniques have been described, with the method proposed by Jothikumar et al in 2006, one of the most frequently used because of its high specificity and sensitivity [49,50].…”
Section: Introductionmentioning
confidence: 99%